A tale of sorcery... - Colfer, Chris, 1990-; Dorman, Brandon (New York : Little, Brown and Company, 2021)
The Southern Kingdom is in the grip of Emperor Seven and his war on both magic, books, and learning. Even worse, a malignant darkness is rising and threatening everybody, including Brystal Evergreen, who has gathered allies among the fairies and other magical creatures to confront the threat. She is also aware that the days of her life are slipping away, and if she does not find the Book of Sorcery in a few weeks she will die.
3-6.
6.4.
830L
Keywords: Magic -- Juvenile fiction; Witches -- Juvenile fiction; Fairies -- Juvenile fiction; Good and evil -- Juvenile fiction; Books and reading -- Juvenile fiction; Magic -- Fiction; Witches -- Fiction; Fairies -- Fiction; Good and evil -- Fiction; Books and reading -- Fiction; Fantasy; Fantasy fiction